Representation of the Values ​​of Peace, Justice, and Conflict Resolution: A Discourse Analysis of Arabic Language Textbooks in Madrasahs - Kuraedah, St; Mar, Nur Azaliah; Zulaeha, Zulaeha; Muna, Wa (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study examines the representation and pedagogical potential of peace and social justice values in Arabic textbooks used at the Madrasah Tsanawiyah (MTs) in Indonesia. Grounded in Johan Galtung’s concept of positive peace, John Paul Lederach’s conflict transformation framework, UNESCO’s pillars of peace education, and social constructivist theory, the study explores how textbooks contribute to students’ peace consciousness and peace-oriented learning. Using a qualitative design, critical content analysis was applied to Arabic language textbooks for Grades VII, VIII, and IX published by the Indonesian Ministry of Religious Affairs. 18 texts were analyzed through thematic coding, focusing on non-violence, empathy, tolerance, equality, and social justice. The findings indicate that peace values are predominantly represented through harmonious interpersonal relations, politeness, empathy, and cooperation, reflecting an understanding of peace primarily as social harmony. However, more complex dimensions of peace, such as social justice, conflict resolution, pluralism, and structural inequality, are marginal and insufficiently articulated. Pedagogically, the textbooks provide limited opportunities for dialogical and reflective learning. Nevertheless, the consistent presence of relational peace values suggests considerable potential for strengthening peace education through intentional teacher mediation and constructivist pedagogical approaches.